PERJANJIAN SEWA MENYEWA BENDA BERGERAK: TIMBULNYA WANPRESTASI AKIBAT PEMINJAMAN MOBIL - Gabriela Priscila Br Sitepu; Venesia Anandita Mulya; Luqiana Halawati; Ruth Destyaningrum; Dwi Aryanti Ramadhani (Cahaya Ilmu Bangsa, 2024)
In everyday life, of course, there will always be legal events that occur, even for a party who owns objects (lessor) often conducts what is called a lease agreement to the lessee. Lease agreements arise because of the existence of legal subjects who are born to carry out these events. The lease agreement involves an agreement on movable or immovable property belonging to the owner of the object (lessor) to the tenant (lessee) which in the case of this agreement also has applicable terms and conditions given to the tenant. For the lessee, if he commits a default that results in negligence in terms of delaying payments, borrowing and even causing damage to the object, he must be responsible for resolving this matter. In this case, CV. GH Tour and Travel is a place to rent a rental car vehicle. However, it turns out that the object of the lease experienced negligence in the form of delays in returning and damage to car parts and car parts which ultimately made the CV. GH Tour and Travel suffered material and immaterial losses so that because of this damage the tenant must pay losses. Therefore, the emergence of this case will be the subject of discussion to be able to follow up this case in the form of a useful study to be read carefully for all of us.